Identification of early-age concrete temperatures and strains : monitoring and numerical simulation - Azenha, Miguel (2009)
Concrete at early-ages experiences thermal deformations due to the heat generation caused by the cement hydration reactions. These deformations may lead to cracking of concrete, for which the use of numerical models in order to foresee and prevent this problem is of crucial importance. However, these numerical models must be appropriately validated by monitoring the young concrete behaviour. The conducted research regards an experimental work carried out with two main goals: (i) to evaluate the performance of different kinds of strain gages, in order to determine the more adequate ones for monitoring concrete deformations during early-ages after casting; (ii) to interpret the experimental measurements of temperatures and strains in concrete, by using a numerical model. Two different vibrating wire strain gages were used to measure early-age deformations in a concrete prism tested in the laboratory: one with a metallic housing and the other with a plastic one. The instant of solidarization of the sensors to concrete and the temperature sensitivity of their signals during the pre-solidarization period are key points as far as measurement of concrete early-age strains is concerned, which were examined for the present work. A thermo-mechanical numerical model was used to simulate the early-age concrete behaviour of the specimen. After a brief description of the model background, a comparison of the numerical predictions with the experimental results is made.